Analysis of Risk Factors Influencing the Incidence of Breast Cancer at Muhammadiyah Palembang Hospital - Lulu Salsabila; Fadillah Sayuti; Siti Rohani (JURNAL KEDOKTERAN RAFLESIA, 2026)
Breast cancer is a malignant disease that originates in the glandular ducts and supporting tissues of the breast and spreads to other regions of the body through a process known as metastasis. Age, hereditary factors, and dietary patterns contribute to an increased risk of developing breast cancer. This study aimed to evaluate the relationship between age, genetic variables, dietary patterns, and the incidence of breast cancer at the surgical outpatient clinic of Muhammadiyah Palembang Hospital. This study employed an observational analytic approach with a cross-sectional design. The population consisted of patients presenting with breast lumps, with a total of 45 respondents selected through purposive sampling. The findings indicated that 68.9% of the respondents were diagnosed with breast cancer, whereas 31.1% were not. Regarding age, 62.2% of the respondents were aged >40 years and had breast cancer, while 37.8% were aged ≤40 years and did not. Furthermore, 51.1% of the respondents had a family history of breast cancer and were affected by the disease, whereas 48.9% were not. In terms of dietary patterns, 37.8% of the respondents were categorized as having a high-risk diet, and 62.2% were classified as non-high risk. Statistical analysis demonstrated a significant association between age and breast cancer incidence (p < 0.001), as well as between hereditary factors and breast cancer incidence (p = 0.019). Conversely, dietary patterns were not significantly associated with the incidence of breast cancer (p = 0.235). In conclusion, age and hereditary factors are significantly associated with the occurrence of breast cancer, whereas dietary patterns show no significant association.